Pengelolaan Sarana Pembelajaran pada SD Negeri Belah I Donorojo Pacitan - Luqman Hadi (Transformasi : Jurnal Studi Agama Islam, 2017)
The  objectives  of  the  research  are  to  describe  the  characteristics  of:  1)  the  learning facilities  planning;  2)  the  utilities  of  learning  facilities;  and  3)  the  maintenance  of  learning facilities at SDN Belah I Donorojo Pacitan to facilitate the teaching and learning process. The type  of  the  research  is  qualitative  research.  The  design  of  the  research  employed  was ethnographic  study.  The  data  collecting  method  was  done  using  in-depth  interviewing, observation,  and  document  techniques.  The  data  analysis  was  done  using  single  case  analysis design. The analysis design selection  for qualitative research  conveys three main components, namely  data  reduction,  data  display,  and  verification.  The  data  validity  is  done  using triangulation, key informant review and member-check techniques. The research concludes that: 1) the characteristics of learning facilities planning at SDN Belah  I  Donorojo  Pacitan  was  initiated  by  arranging  proposal  proposed  to  get  the  aids  from Ministry  of  Education,  Provincial  Budgetting,  and  Municipal’s  Budgetting.  The  learning facilities  development  was  done  within  the  establishment  of  15  programs  of  school’s  learning facilities. The school learning facilities were financed through school’s budgetting. Th e finance were allocated from parental aids and governmental aids in the form of block grant schemes; 2) The  learning  facilities  utilities  at  SDN  Belah  I  Donorojo  Pacitan  were  done  optimally.  The learning  facilities  were  utilitized  as  students’  competence  exploration  tools,  namely  used  as students’ creativities and innovation tools. The learning facilities controlling strategies were done by  teacher  that  specifically  assigned  to  manage  the  school’s  learning  facilities;  and  3)  the learning  facilities  maintenance  of  multimedia  laboratory  was  done  cooperatively  with  the computer suplier by special contract system. It is done with the effectivity consideration so that the  teacher  may  focus  their  attention  in  teaching  and  learning  process  and  the  facilities  wer e ready to be used at any time.